2015
DOI: 10.4172/2157-7617.1000312
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Weather Forecasting Needs of Smallholder Farmers for Climate Change Adaptation in the Central Rift Valley of Ethiopia

Abstract: In Ethiopia, climate change is set to hit the agricultural sector adversely and cause considerable negative impacts particularly for smallholder farmers. Weather information is one of the requirements for effective climate change adaptation in Ethiopia, where Agriculture is the back bone of the economy. This study made during 2011/12 investigates whether smallholder farmers, development agents and organizations in the Central Rift Valley of Ethiopia have access to weather information and consequently use it in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…In this direction, Inwood and Dale [31], also found a need for mobile applications as a digital decision support tool for emphasizing knowledge exchange rather than just some information delivery. However, in sub-Saharan Africa, Feleke [59], found that more than half of the farmers still depend on the radio as the preferred communication platform. A few model farmers knew about the technology and its uses in sub-Saharan Africa.…”
Section: What Kind Of Information Is Needed By Farmers?mentioning
confidence: 99%
See 1 more Smart Citation
“…In this direction, Inwood and Dale [31], also found a need for mobile applications as a digital decision support tool for emphasizing knowledge exchange rather than just some information delivery. However, in sub-Saharan Africa, Feleke [59], found that more than half of the farmers still depend on the radio as the preferred communication platform. A few model farmers knew about the technology and its uses in sub-Saharan Africa.…”
Section: What Kind Of Information Is Needed By Farmers?mentioning
confidence: 99%
“…Initial engagement of farmers through the farmers' field school (FFS) provided an excellent opportunity for service coproduction in a participatory way where users discussed their specific needs, accessibility, relevance, and particular usage [6]. Results revealed that farmers often had difficulty expressing their needs, particularly as they were not familiar with hydroclimatic information services and have limited or no academic literacy [46,59]. However, the FFS platform helped towards addressing this issue through weekly interaction and participatory training with the help of the local extension office.…”
Section: Farmers' Engagement Processmentioning
confidence: 99%
“…Dissemination of climate services through the radio has no fixed time, implying that to get the information farmers have to turn on their radio, perhaps for the entire day, and thus this may not be an effective means to disseminate the information to all farmers since they have their own setting under which they operate and likely to miss the information when they are busy with some other engagements (Feleke, 2015). The improved hypothetical media included i)…”
Section: Choice Experiments Designmentioning
confidence: 99%
“…This tradition is replicated throughout Kenya due to the fact that majority of the population do not understand weather and climate information in a format in which it is released to the public. Most weather forecast are issued in probabilistic terms such as "chance of", "likelihood", which is not understandable to a common man [15,47]. Nevertheless, residents of Kisii County have resorted to a number of ways of adapting to weather and climate stresses such as soil and water conservation measures, planting different variety of crops and changing planting dates according to rainfall onset dates.…”
Section: Discussionmentioning
confidence: 99%